Theoretical Study to Predict the Ability to Use Different Organic Substituents as Carrier Linkages for Diclofenac - Majed Kubba, Rehab; Muthana Shanshal, Aisha (Asian Journal of Chemistry, 2021)
The research includes unrestricted (UDFT) and (UPM3) quantum mechanical calculations for studying the reaction path of bonds rupture energies of (O-R) and (C-OAr) in twelve diclofenac derivatives containing different substituted organic groups. All the calculations were performed at the optimize geometries in vacuum phase by using Gaussian 09 program. Comparison was done between the studied diclofenac derivatives and the standard ionic diclofenac of sodium and potassium included geometrical structures, physical properties, total energies of the reactants and products, activation energies and transition states. The results showed that some substituted organic groups could be used to form good carrier bonds for the acidic drug diclofenac, while others were less efficient depending on the nature of the substituted carrier, and that there is a preference for carriers of the type (–R) over the carriers of the type (–Ar).